2017
DOI: 10.21037/hbsn.2017.01.20
|View full text |Cite
|
Sign up to set email alerts
|

Modelling western dietary habits in the mouse: easier said than done

Abstract: The recent debate on the relative importance of environmental vs. intrinsic factors in the onset of malignancy has raised major concerns that the general public might conclude that cancer prevention programmes are not worthwhile. In their original report (1), Tomasetti and Vogelstein concluded that a majority of cancers can be explained by the high number of stem cell divisions in tissues with a high cell turn-over, due to generation of random mutations and their accumulation each time DNA replicates. In a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Current Protocols in Toxicology can play a role in data interpretation when both are used in the same study. The problem with using a GB diet as a control diet for a high fat purified ingredient diet has been discussed and recent surveys suggest this problem still can be found in many studies (Fodde, Schmitt, Schewe, & Augenlicht, 2017;Pellizzon & Ricci, 2018;Rendina-Ruedy & Smith, 2016;Warden & Fisler, 2008). In a recent survey of 69 publications including Cell, Nature, and Diabetes using search terms 'mouse high fat', it was found that only 18.8% of studies used a matched purified ingredient low fat control diet for the high fat diet while 40.6% used a GB diet as the low fat 'control' diet, with the remaining 40.6% of papers not providing sufficient data to determine what control diet was used (Pellizzon & Ricci, 2018).…”
Section: Of 14mentioning
confidence: 99%
“…Current Protocols in Toxicology can play a role in data interpretation when both are used in the same study. The problem with using a GB diet as a control diet for a high fat purified ingredient diet has been discussed and recent surveys suggest this problem still can be found in many studies (Fodde, Schmitt, Schewe, & Augenlicht, 2017;Pellizzon & Ricci, 2018;Rendina-Ruedy & Smith, 2016;Warden & Fisler, 2008). In a recent survey of 69 publications including Cell, Nature, and Diabetes using search terms 'mouse high fat', it was found that only 18.8% of studies used a matched purified ingredient low fat control diet for the high fat diet while 40.6% used a GB diet as the low fat 'control' diet, with the remaining 40.6% of papers not providing sufficient data to determine what control diet was used (Pellizzon & Ricci, 2018).…”
Section: Of 14mentioning
confidence: 99%